2015
DOI: 10.1111/cea.12329
|View full text |Cite
|
Sign up to set email alerts
|

Transportation of sublingual antigens across sublingual ductal epithelial cells to the ductal antigen‐presenting cells in mice

Abstract: This study reveals that sublingual antigens can be transported across sublingual ductal epithelial cells to the ductal APCs. If the system is the same in humans as in mice, the ductal APCs may prove to be important target cells for SLIT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 25 publications
3
23
0
Order By: Relevance
“…In our investigation, we observed Si beads accumulating in the apical cytoplasm of some cells lining the sublingual ducts but not in the mandibular ducts. This observation is supported by a previous report concerning the role of the sublingual ductal system in incorporating and delivering sublingual antigens to ductal antigen-presenting cells [18]. Interestingly, in this previous report M cells were observed in the gastrointestinal mucosa and demonstrated the ability to take up antigen by phagocytosis [30, 31].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In our investigation, we observed Si beads accumulating in the apical cytoplasm of some cells lining the sublingual ducts but not in the mandibular ducts. This observation is supported by a previous report concerning the role of the sublingual ductal system in incorporating and delivering sublingual antigens to ductal antigen-presenting cells [18]. Interestingly, in this previous report M cells were observed in the gastrointestinal mucosa and demonstrated the ability to take up antigen by phagocytosis [30, 31].…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, a recent report revealed the role of APCs in sublingual ductal epithelial cells in the transportation of sublingual antigen. This was shown using soluble antigens such as ovalbumin and particulate antigens such as E. coli, latex beads (Lt) and silica beads (Si) [18]. Moreover, it has been revealed that bacterial infection of the salivary glands may result from bacteria ascending through salivary gland ducts and stasis of salivary flow through the ducts [19].…”
Section: Introductionmentioning
confidence: 99%
“…Supporting this route also for PM‐allergoids is the response obtained in submandibular LNs, the primary draining lymph nodes of sublingual tissue 24. In this sense, besides antigen penetration across the sublingual epithelial barrier, an active capture by intraepithelial DCs25 or through the ductal epithelial cells26 has been described, even for particulate antigens, silica beads, or microbes 26. In fact, bigger structures than PM‐allergoids, like particles of different sizes15, 27 or whole cell bacteria,28, 29 have also been successfully used for immunization through the sublingual route.…”
Section: Discussionmentioning
confidence: 92%
“…Compared to other routes, the sublingual and buccal routes have the potential to induce mucosal immune responses in a broad range of tissues (Table 1) as described in more detail in Section 2.2 ('Mucosal immune responses'). Nagai et al (2014) recently reported the transport of sublingual antigens across sublingual ductal epithelial cells to ductal APCs in mice [14]. Since different studies failed to detect specific sampling cells (or M-like structures) in the sublingual or buccal mucosa [14,15], it seems most likely that antigens cross the ductal epithelium via paracellular and transcellular pathways [14].…”
Section: Implications For Mucosal Vaccine Delivery and Comparison Witmentioning
confidence: 99%
“…Nagai et al (2014) recently reported the transport of sublingual antigens across sublingual ductal epithelial cells to ductal APCs in mice [14]. Since different studies failed to detect specific sampling cells (or M-like structures) in the sublingual or buccal mucosa [14,15], it seems most likely that antigens cross the ductal epithelium via paracellular and transcellular pathways [14]. So, probably the efficiency of vaccine delivery via these routes is directly related to the permeability of the mucosal membrane.…”
Section: Implications For Mucosal Vaccine Delivery and Comparison Witmentioning
confidence: 99%